Visualization of flow boiling heat transfer using temperature sensitive paint with high spatial and temporal resolution. (15th November 2022) - Baba, Soumei; Saito, Shimpei; Takada, Naoki; Someya, Satoshi
Highlights: A new method for visualization of boiling surface temperature profiles has been developed using a temperature-sensitive paint (TSP) film structure and pulsed LED excitation to enhance emission intensity. The temperature of the heat transfer surface in forced flow boiling was visualized with a spatial resolution of 64 µm and measurement speed of 2 kHz. The unsteady changes in the temperature and the heat transfer coefficient due to expansion of the dry patches at the bottom of the nucleated small bubble and slug bubble were evaluated. Abstract: Boiling heat transfer plays an important role in a wide range of industrial applications. Recent advances in optical measurement technology have made possible the visualization of the heat transfer distribution on the heating surfaces. We designed a multilayer structure of temperature sensitive paint (TSP) and transparent heating layer on a heat transfer surface to measure boiling heat transfer with high-speed visualization. A TSP layer containing a fluorescent material, platinum porphyrin (PtTFPP), was formed on a heat transfer surface, and a forced flow boiling experiment was conducted using HFE-7000 as the test fluid. The temperature of the heat transfer surface was visualized with a spatial resolution of 64 µm and measurement speed of 2 kHz under a mass velocity of 104 kg/(m 2 ·s) and average heat flux of 96 kW/m 2 . We observed a high temperature area underneath the nucleated vapor bubbles on the heat transfer surface possibly due to heat transfer degradation caused by expansion of dry patches and a low temperature area around the vapor bubbles due to convective heat transfer in the liquid layer. We found that the temperature distribution at the bottom of the bubbles followed the growth and movement of the bubbles. In addition, we demonstrated that it is possible to quantitatively evaluate the unsteady heat transfer coefficient distribution when a dry zone is created at the bottom of large slug bubbles.